Menelusuri Perdebatan Kontemporer Pada Doktrin Pilihan Karl Barth - Richard Richard; Denni Boy Saragih (Jurnal Silih Asuh : Teologi dan Misi, 2024)
Karl Barth's statement in his doctrine of Election regarding Jesus Christ being the subject and object of God’s election, sparked a conversation among Barth’s scholars in the academic world. This paper aims to show the dynamics of the debate and find the main points of the debate. Using a literature review method of the debates, it will be shown that there is an issue of God's freedom in unity between immanent and economic God. In this case, McCormack is able to offer God's freedom by uniting immanent and economic God.